Ly6Chigh Monocytes Oscillate in the Heart During Homeostasis and After Myocardial Infarction—Brief Report. Issue 9 (September 2017) - Schloss, Maximilian J.; Hilby, Michael; Nitz, Katrin; Guillamat Prats, Raquel; Ferraro, Bartolo; Leoni, Giovanna; Soehnlein, Oliver; Kessler, Thorsten; He, Wenyan; Luckow, Bruno; Horckmans, Michael; Weber, Christian; et al.
Abstract : Objective—: Circadian regulation of neutrophil homeostasis affects myocardial infarction (MI) healing. It is unknown whether diurnal variations of monocyte counts exist in the heart and whether this affects their cardiac infiltration in response to MI. Approach and Results—: Murine blood and organs were harvested at distinct times of day and analyzed by flow cytometry. Ly6C high monocyte surface expression levels of chemokine receptors (CCR) were ≈2-fold higher at the beginning of the active phase, Zeitgeber Time (ZT) 13 compared with ZT5. This was because of enhanced receptor surface expression at ZT13, whereas no significant changes in total cellular protein levels were found. Most blood Ly6C high monocytes were CCR2 high, whereas only a minority was CCR1 high and CCR5 high . We also found diurnal changes of classical monocyte blood counts in humans, being higher in the evening, while exhibiting enhanced CCR2 surface expression in the morning. In support of monocyte oscillations between blood and tissue, murine cardiac Ly6C high monocyte counts were highest at ZT13, accompanied by an upregulation of cardiac CC chemokine ligand 2 mRNA. Mice subjected to MI at ZT13 had an even higher upregulation of CCR2 surface expression on circulating monocytes compared with noninfarcted mice and more elevated cardiac CC chemokine ligand 2 protein expression and more pronounced Ly6C high monocyte infiltration compared with ZT5-infarcted mice. Concomitantly, CCR2 antagonism only inhibited the excessive cardiac Ly6C high monocyte infiltration after ZT13 MI but not ZT5 MI. Conclusions—: CCR2 surface expression on Ly6C high monocytes changes in a time-of-day–dependent manner, which crucially affects cardiac monocyte recruitment after an acute ischemic event. Abstract : Supplemental Digital Content is available in the text.